An inflammatory myofibroblastic tumor of the small intestine in a 15-year-old girl - Xiao Yu; Mao-mao Zhao; Hao Guo; Pei-you Gong; Jun-xia Li; Yun-qiang Wang (Turkish Journal of Gastroenterology, 2019)
-